IMPLEMENTATION OF POLICIES FOR THE MODERNISATION OF TRADITIONAL MARKETS IN TELUK KUANTAN, KUANTAN SINGINGI DISTRICT - Anesa, Fitri; Meilani, Nur Laila (TOPLAMA, 2025)
The purpose of this study is to find out how the implementation of the modern-based traditional market arrangement policy in Teluk Kuantan, Kuantan Singingi Regency uses Edward III's theory of Communication, Resources, implementer attitudes, and bureaucratic structure. This study uses qualitative methods and data collection techniques, namely observation, interviews, and documentation. Based on the results of the study, it can be concluded that the implementation of the modern-based traditional market arrangement policy in Teluk Kuantan, Kuantan Singingi Regency has been running optimally, this is evidenced by the communication that has been running well, including the Cooperatives, Small and Medium Enterprises, Trade, Industry Office has had consistency in efforts to convey information to the public by conducting socialization and reviews related to the arrangement of market locations. Human resources are well-functioning, as evidenced by the Department of Cooperatives, Small and Medium Enterprises, Trade, and Industry's commitment to providing services to the public, as evidenced by comfortable office facilities. The attitude of the implementers, in this indicator, has been well-functioning. This can be seen from the professionalism of the employees and their provision of good service to the public. The bureaucratic structure has not been implemented well, as evidenced by the established Standard Operating Procedures (SOPs) and the unachieved policy targets. The recommendation from this study is for the government to effectively disseminate information about traditional market management to increase public understanding. It is hoped that traders will follow and accept the policies implemented by the Department of Cooperatives, Small and Medium Enterprises, Trade, and Industry.